THE INFLUENCE OF BRAND PERCEPTION ON THE DECISION TO USE JNE EXPRESS DELIVERY SERVICES WITH CONSUMER ATTITUDES AS AN INTERVENING VARIABLE (Case Study on JNE Customers (Nugraha Ekakurir Line) Pematang Siantar City) - Yulianita Lubis, Siska; Mazdalifah, Nur; Sihombing, Eka; Mareny, Riada; Wardati, Jumadiah (Universitas Efarina, 2022)
This study aims to find out how the influence of brand perception on the decision to use JNE express delivery services with consumer attitudes as an intervening variable. The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The method of data analysis in this study uses simple linear regression analysis to obtain a comprehensive picture of the influence between the variables Brand Perception and the Decision to Use Services by using the SPSS 25 for Windows program. To find out whether there is a significant effect of the independent variable on the dependent variable, a simple linear regression model is used. The results of hypothesis testing using simple regression analysis and t-test show that: